Evaluation of selected cowpea varieties under competition with weeds (Revista Ciência Agronômica, 2021)
Cowpea is cultivated in the semi-arid region of Brazil and in various other countries, generally employingtraditional varieties, which are grown as intercrops by low-income, illiterate farmers who lack technical assistance. Under suchconditions, the use of herbicides is limited, and weed control is usually carried out by hoeing. Combining more varieties thatare more competitive against weeds, and planting at higher planting densities using different cropping practices could reducethe work of weeding. In a preliminary study, 48 traditional varieties of the cowpea were grown with only one weeding, andevaluated for dry-grain yield. The aim of the present study was to evaluate the green- and dry-grain yields of six varieties: three thatproved to be more productive (Umarizal, Itaú and Upanema), and three that had low yields (Mossoró, Santa Cruz and São Miguel) in thepreliminary evaluation. The varieties were submitted to two types of weed-control management (one or two weedings). A randomisedblock design was used, in split plots with five replications. Weed management was applied to the plots, and the traditionalvarieties to the subplots. It was found that, in terms of the effect on the yields under evaluation, there was no difference in thenumber of weedings. The Umarizal, Itaú, Upanema and Mossoró varieties were the best for green-grain production, with thefirst two also being superior in the production of dry grain.